The use of starch with the addition of glauconite to create nanocomposite packaging materials - Mank, Valeriy; Melnyk, Oksana (My University, 2012)
We consider of film materials from annually renewable components – the starch with the addition of clay mineral glauconite in the form of nanoparticles and investigated their mechanical properties.
Keywords: starch; glauconite; adsorption; packaging materials; крохмаль; глауконіт; адсорбція; пакувальна плівка; крахмал; глауконит; адсорбция; упаковочная пленка; кафедра технології жирів, хімічних технологій харчових добавок та косметичних засобів; кафедра експертизи харчових продуктів